Factors Associated With Short-Term Eradication of Rectal Colonization by KPC-2 Producing Klebsiella pneumoniae in an Outbreak Setting - Pellicé, Martina; Rodríguez-Núñez, Olga; Rico, Verónica; Agüero, Daiana; Morata, Laura; Cardozo, Celia; Puerta-Alcalde, Pedro; Garcia-Vidal, Carolina; Rubio, Elisa; Fernandez-Pittol, Mariana J.; Vergara, Andrea; Pitart, Cristina; et al. (Frontiers in Microbiology, 2021)
Background: KPC-producing Klebsiella pneumoniae (KPCKP) is a threat for patients admitted to healthcare institutions. Objectives: To assess the efficacy of several decolonization strategies for KPCKP rectal carriage. Methods: Observational study performed in a 750-bed university center from July to October 2018 on the efficacy of a 10-day non-absorbable oral antibiotic (NAA) regimen (colistin 10 mg/ml, amikacin 8 mg/ml, and nystatin 30 mg/ml, 10 ml/6 h) vs. the same regimen followed by a probiotic (Vivomixx®) for 20 days in adult patients with KPCKP rectal colonization acquired during an outbreak. Results: Seventy-three patients colonized by KPCKP were included, of which 21 (29%) did not receive any treatment and 52 (71.2%) received NAA either alone (n = 26, 35.6%) or followed by a probiotic (n = 26, 35.6%). Eradication was observed in 56 (76.7%) patients and the only variable significantly associated with it was not receiving systemic antibiotics after diagnosis of rectal carriage [22/24 (91.6%) vs. 34/49 (69.3%), p = 0.04]. Eradication in patients receiving NAA plus probiotic was numerically but not significantly higher than that of controls [23/26 (88.4%) vs. 15/21 (71.4%), p = 0.14] and of those receiving only NAA (OR = 3.4, 95% CI = 0.78–14.7, p = 0.09). Conclusion: In an outbreak setting, rectal carriage of KPCKP persisted after a mean of 36 days in about one quarter of patients. The only factor associated with eradication was not receiving systemic antibiotic after diagnosis. A 10-day course of NAA had no impact on eradication. Probiotics after NAA may increase the decolonization rate, hence deserving further study.